P107 Patient self-reported sleep quality, noise and light levels in a tertiary ICU: a prospective observational study. (7th October 2021) - Martinez, F; Seneviratne, C; Chrimes, A; Paech, G
Abstract: Introduction: Sleep is poor in intensive care units (ICU). However, there is limited research examining the causes from the patient perspective, especially in an Australian population. The current study investigated the factors that patients perceive as affecting their sleep in a major Australian tertiary ICU. Methods: Patients (n=138, 51F; aged 58.1±16.8 years) completed a survey assessing sleep before and during their ICU stay, factors contributing to poor sleep, and factors that may have improved their sleep in the ICU. Night-time sound (16 nights) and light (28 nights) levels in rooms were also measured. Results: Most patients reported good (38%) to very good (25%) sleep quality before their ICU stay, and poor (28%) to very poor (32%) sleep quality in the ICU. Over half (56%) reported an abnormal sleep-wake cycle and most (60%) felt as though they did not obtain sufficient sleep. Noise (54%), pain (50%) and lights (48%) were the top reasons for self-reported poor sleep. Patients felt as though their sleep would have been improved with dimmed lights (64%), a sleeping pill (57%) and closing door/blinds at night (46%). Median (IQR) overnight noise and light levels were 52.8 (51.4–54.6) dB and 39.9 (8.2–90.9) lux respectively. Discussion: Of the top three factors that patients perceive to be the primary reasons for poor sleep, two are modifiable (noise and lights). Night-time sound levels exceed standard recommendations and light levels, while mostly low, were higher than indicated for a healthy sleep environment, suggesting that these could be modified to improve patients sleep.